Plasticity‐led evolution: A survey of developmental mechanisms and empirical tests. Issue 1 (26th August 2019) - Levis, Nicholas A.; Pfennig, David W.
Abstract: Recent years have witnessed increased interest in evaluating whether phenotypic plasticity can precede, facilitate, and possibly even bias adaptive evolution. Despite accumulating evidence for "plasticity‐led evolution" (i.e., "PLE"), critical gaps remain, such as: how different developmental mechanisms influence PLE; whether some types of traits and taxa are especially prone to experience PLE; and what studies are needed to drive the field forward. Here, we begin to address these shortcomings by first speculating about how various features of development—modularity, flexible regulation, and exploratory mechanisms—might impact and/or bias whether and how PLE unfolds. We then review and categorize the traits and taxa used to investigate PLE. We do so both to identify systems that may be well‐suited for studying developmental mechanisms in a PLE context and to highlight any mismatches between PLE theory and existing empirical tests of this theory. We conclude by providing additional suggestions for future research. Our overarching goal is to stimulate additional work on PLE and thereby evaluate plasticity's role in evolution. Abstract : Plasticity‐led evolution has gained increasing support. For example, eastern spadefoot toad tadpoles, Scaphiopus holbrookii, normally eat plankton and detritus, but they occasionally ingest large animal prey; this individual is cannibalizing a conspecific. This shift from plant‐based to meat‐based diet induces changes in gene expression and trophic morphology, which might have jump started the evolution of a distinctive carnivore morph found in other species of spadefoot toads. This paper surveys the types of traits and taxa used to study plasticity‐led evolution, and it explores hypotheses of how various developmental mechanisms might influence whether and how plasticity‐led evolution unfolds. It concludes with a list of suggestions for future work on this problem. Research highlights: We explore how various developmental processes—modularity, flexible regulation, exploratory mechanisms—impact plasticity‐led evolution (PLE). We also review the traits and taxa used to test PLE to identify any mismatches between theory and data.